FERDINAND DE SAUSSURE'S SEMIOTIC ANALYSIS ON DJOKO PEKIK'S “GO TO HELL CROCODILLE” PAINTING - Semara Putra, Edy (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
This study aims to identify and interpret the symbolic meaning embedded in Djoko Pekik’s painting Go to Hell Crocodile through the semiotic framework of Ferdinand de Saussure. The painting is recognized as a significant work in contemporary Indonesian art that conveys social criticism through symbolic visual language. While previous studies have examined this artwork from formal and aesthetic perspectives, research applying Saussure’s structural semiotic approach remains limited. This research employed a qualitative design using a semiotic analysis method. Data were collected through visual observation, documentation, and literature review. The analysis was conducted by identifying visual elements as signifiers, determining their conceptual meanings as signified, and examining the relationships between these elements within relevant social and cultural contexts. The findings indicate that visual elements such as the crocodile figure, spiral ground patterns, crowds of people, pointed bamboo, traditional Honai houses, and mountainous landscapes form a structured system of signs representing social conflict and power inequality. The interpretation suggests that the painting reflects issues related to natural resource exploitation, social resistance, and socio-political dynamics in Indonesian society. This study confirms that artworks function as visual communication systems capable of conveying complex social messages through symbolic representation and demonstrates the relevance of Saussure’s semiotic theory in the analysis of contemporary visual art.